Comparison of Chang’s with Sorenson’s attenuation correction method by varying linear attenuation coefficient values in Tc-99m SPECT imaging - Sayed, Inayatullah Shah; Zakaria, Ahmed; Nik, Norhafiza (Springer-Verlag Berlin Heidelberg, 2008)
Attenuation (scattering and absorption) of gamma photons in the patient’s body is one of the major limitations among the others in single photon emission computed tomography (SPECT). It reduces quantitative accuracy of measured radioactivity concentration and causes hot rim artifacts in reconstructed images if not corrected for. A variety of approximate attenuation correction methods has been developed or proposed by various groups to date,but all methods have some limitations. In this paper two attenuation correction methods have been investigated and compared. Data are acquired with both the collimators either LEGP or LEHR by scanning R. A. Carlson cylindrical phantom over 360o with an acrylic block of holes simulating hot regions of various sizes at different locations with respect to the walls of the phantom,which was filled with water and Tc-99m solution was uniformly distributed. Results show that the Chang’s attenuation correction method works better as compared to the Sorenson’s method in terms of the linearity in measured counts in hot regions. However, Chang’s method is sensitive with linear attenuation coefficient values and also gives higher standard deviation values particularly in smaller hot regions count density – with LEHR collimator data - compared to the Sorenson’s method.